Unlocking The Secret of E-Loyalty: A Study from Tiktok Users in China - Susilo, Donny (FEB - Universitas Lampung, 2020)
TikTok is a recent global phenomenon and in the first quarter of 2020 alone it has TikTok been downloaded 315 million times. People love it because it allows them to spur creativity in video content and increase their online presence. Founded by a Chinese company, this social networking application has become a trend for about 400 million loyal users in China. However, studies about how people become loyal to TikTok are lacking. This study aims to examine the effect of service quality and satisfaction to loyalty of TikTok users in China. Since the study was focused in an online environment, the terms E-service quality, E-satisfaction and E-loyalty are used instead of the conventional ones. SEM-PLS was employed to analyze valid and reliable data which was successfully collected from 400 Chinese TikTok users. The result confirmed that E-service quality affects significantly and positively E-satisfaction and E-loyalty, E-satisfaction also significantly and positively affects E-loyalty and E-satisfaction mediates the relationship between E-service quality and E-loyalty. Since the TikTok application is easy to use with interesting features for its users, the company has successfully delivered information about the booming of TikTok use all over the world and impressing users so that they have high trust in the application’s ability to make them more famous and socially famous. Therefore users believe that TikTok can provide them something better than what they expected. When reality exceeds the expectation, customers will be satisfied. TikTok is also believed to have a good, reliable and available system.